Sars - Davis, Deborah; Siu, Helen F. (Routledge Contemporary China Series, 2007)
SARS (Acute Respiratory Syndrome) first presented itself to the global medical community as a case of atypical pneumonia in one small Chinese village in November 2002. Three months later the mysterious illness rapidly spread and appeared in Vietnam, Hong Kong, Toronto and then Singapore. The high fatality rate and sheer speed at which this disease spread prompted the World Health Organization to initiate a medieval practice of quarantine in the absence of any scientific knowledge of the disease. Now three years on from the initital outbreak, SARS poses no major threat and has vanished from the global media. Written by a team of contributors from a wide variety of disciplines, this book investigates the rise and subsequent decline of SARS in Hong Kong, mainland China and Taiwan. Multidisciplinary in its approach, SARS explores the epidemic from the perspectives of cultural geography, media studies and popular culture, and raises a number of important issues such as the political fate of the new democracy, spatial governance and spatial security, public health policy making, public culture formation, the role the media play in social crisis, and above all the special relations between the three countries in the context of globalization and crisis. It provides new and profound insights into what is still a highly topical issue in today's world.